ANALYSIS OF REGIONAL INEQUALITY IN THE PROVINCE OF MALUKU - Uguy, Leroy Samy; Kembauw, Esther; Kakisina, Anrey P.; Kembauw, Marthina G. I. (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study aims to determine the extent of regional inequality in Maluku Province, and to determine the factors that influence regional inequality such as population, education, health, regional labor. The analysis method used to see regional inequality is the Williamson Index. Meanwhile, Panel Data Regression is used to analyze the factors that influence inequality. Based on the results of the Williamson Index calculation, the inequality of Maluku Province is in the medium category at 0.45, the highest regional inequality is Aru Regency and Buru Regency. Furthermore, the results of Panel Regression with the fixed effect data model show that Population, Education, Health, Labor variables simultaneously affect regional inequality, while partially Population and Education have a positive effect at a significance level of Î± = 5% (95% confidence level). The coefficient of determination (R2) of 98% indicates that the specification of the regression model used is appropriate and has goodness of fit. Policy recommendations for overcoming inequality should prioritize human development, furthermore, to reduce regional inequality in Maluku Province, development is carried out in the areas of highest inequality, namely Aru Regency and Buru Regency.